Analisis Keterkaitan Pemerintah Pusat dalam Peningkatan APBN dan APBD Tahun Anggaran 2023 - Ervan Ginting; Shellya Eka Putri; Zito Yonatan Sinaga (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The role of the central government and regional governments is really needed in managing income and empowering resources to increase the State Revenue and Expenditure Budget (APBD) and also the Regional Revenue and Expenditure Budget (APBD). The central government which has control over the APBN is also responsible under it regarding the APBN, although the APBD that manages it is the regional government but it cannot be separates from the cooperation and monitoring of the central government. The aim of this research if to find out about state income as the basis for forming the APBN, the relationship between regional income and the APBN, and the allocation of budget revenues in the APBD. This research method uses library research methods with data analysis techniques using descriptive analysis. The results of this research say that the central and regional goverments must be wise in managing APBN and APBD funds so that the use of APBN and APBD is right on target for national development and the welfare of Indonesian society.